Neutral detergent fibre in piglet diets: digestibility, performance, and deposition of body nutrients - Nepomuceno, Rafael C.; Watanabe, Pedro H.; Freitas, Ednardo R.; Carvalho, Luiz E. De; Oliveira, Emanuela L. De; Gomes, Thalles R.; Aguiar, Germana C.; Candido, Rayssa S.; Ferreira, JordÂnia L.; Veira, Alini M. (Academia Brasileira de Ciências, 2018)
ABSTRACT A total 120 piglets with an average live weight of 7.00 kg, weaned at 21 days, were used to evaluate the effect of neutral detergent fibre levels on the digestibility of nutrients and energy from the diets, productive performance, and the composition and rate of deposition of nutrients and energy in the bodies of piglets in the nursery phase. The animals were distributed according to a randomized-block design into five treatments, which consisted of neutral detergent fibre levels, with six replicates and four animals per plot. A quadratic effect was detected for the digestibility coefficients of nutrients and energy, feed intake and weight gain. The increase in fibre level promoted a linear increase in fat content in the carcass, blood, and body, whereas the energy in the carcass, organs, and body showed an inverse response. The results showed a quadratic effect on the nutrient deposition rate in the carcass, organs and body. In conclusion, the best digestibility of nutrients and energy from the diet is obtained with 10-11.5% neutral detergent fibre, as higher weight gain and greater protein deposition in the body are achieved at neutral detergent fibre levels of 10.6% and 10.3%, respectively.
Keywords: dietary fibre; retention of nutrients; pigs; post-weaning